The Effects of Food Processing on the Archaeological Visibility of Maize: An Experimental Study of Carbonization of Lime-treated Maize Kernels - Dezendorf, Caroline (Ethnobiology Letters, 2013)
This paper explores the effects of maize processing on the carbonization and preservation of maize kernels in the archaeological record. The shift to processing maize with lime (known as hominy production in the Eastern Woodlands and nixtamalization in Mesoamerica) in ancient times had the effect of making maize more nutritious through increasing the availability of calcium, niacin, dietary fiber, and essential amino acids. Less understood is how this process of cooking maize in a lime solution affects the archaeological preservation of maize; if there is a clear difference in the archaeological signature of maize remains that are and are not processed this way, then this process may be identifiable in the archaeological record. To this end, an experiment was constructed analyzing the variation in size between dried and alkali processed maize kernels before and after carbonization. Results indicate that alkali processed maize kernels are less likely to fragment during carbonization.